2019
DOI: 10.1523/jneurosci.1191-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Nociceptor Neuroplasticity Associated with In Vivo Opioid-Induced Hyperalgesia

Abstract: Opioid-induced hyperalgesia (OIH) is a serious adverse event produced by opioid analgesics. Lack of an in vitro model has hindered study of its underlying mechanisms. Recent evidence has implicated a role of nociceptors in OIH. To investigate the cellular and molecular mechanisms of OIH in nociceptors, in vitro, subcutaneous administration of an analgesic dose of fentanyl (30 g/kg, s.c.) was performed in vivo in male rats. Two days later, when fentanyl was administered intradermally (1 g, i.d.), in the vicinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 105 publications
2
28
1
Order By: Relevance
“…Furthermore, cordycepin is described to have anti-inflammatory (reduced synovial inflammation) and analgesic effects in osteoarthritic animal models and in other conditions associated with pain and inflammation. Different mechanisms were proposed to potentially explain the effect of cordycepin on pain behaviour, such as inhibition of inflammatory signalling as well as direct effects on the primary afferent nociceptors [ 42 , 97 , 110 , 121 , 131 , 133 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cordycepin is described to have anti-inflammatory (reduced synovial inflammation) and analgesic effects in osteoarthritic animal models and in other conditions associated with pain and inflammation. Different mechanisms were proposed to potentially explain the effect of cordycepin on pain behaviour, such as inhibition of inflammatory signalling as well as direct effects on the primary afferent nociceptors [ 42 , 97 , 110 , 121 , 131 , 133 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ].…”
Section: Resultsmentioning
confidence: 99%
“…To estimate rheobase, a series of current steps with 200-pA increments was applied until APs were elicited. The protocol was then adjusted to five to six pulses with step size of 5-10% of the rheobase estimate (two to three subthreshold stimuli and two to three with AP generation, to avoid overstimulation/desensitization; Ferrari et al, 2018;Khomula et al, 2019).…”
Section: Culture Of Drg Neuronsmentioning
confidence: 99%
“…We have recently shown that m-opioid receptor (MOR) agonists, including two commonly used clinical opioids, fentanyl (Araldi et al, 2018c;Khomula et al, 2019) and morphine (Araldi et al, 2019;Ferrari et al, 2019), as well as two biased MOR agonists, PZM21 and TRV130 (Araldi et al, 2018a), can produce both OIH and opioid-induced hyperalgesic priming (OIHP). We have recently established an in vitro model of OIH, neuroplasticity induced by in vivo administration of fentanyl that persists in cultured DRG neurons, differentially affecting peptidergic and non-peptidergic nociceptors (Khomula et al, 2019). However, despite a growing literature obtained from in vivo experiments, lack of an in vitro model of OIHP has made it difficult to study underlying mechanisms at the cellular level, in identified nociceptor populations.…”
Section: Introductionmentioning
confidence: 99%
“…Culture of DRG neurons. Primary cultures of DRG neurons were made from adult male Sprague Dawley rats (weight, 220-235 g), as described previously (Ferrari et al, 2016b(Ferrari et al, , 2018Khomula et al, 2017Khomula et al, , 2019Araldi et al, 2019). In brief, under isoflurane anesthesia, rats were decapitated and the dorsum of the vertebral column surgically removed; L4 and L5 DRGs were rapidly extracted bilaterally, chilled, and desheathed in HBSS on ice.…”
Section: Methodsmentioning
confidence: 99%